Plan de promoción de los atractivos turísticos y culturales del cantón Quevedo año 2020 - Manrique Ruiz, Lisbeth Carolina (2021)
The purpose of this project was to carry out a plan to promote the tourist and cultural attractions of the Quevedo Canton by means of an evaluation, it was possible to identify the current state of tourism in the Quevedo Canton and the current situation of the operation of the tourist attractions was analyzed. was able to observe the deficiencies in the services offered to tourists in this way, proposals for their improvement and the correct development of future tourism products arose. One problem that Quevedo still has is that despite having an excellent commercial activity and with the financing of businessmen who have decided to invest in the city due to its economic development, it lacks a tourist promotion and advertising that potentiated this sector. The implementation of a plan to promote tourist and cultural attractions will influence the tourist, cultural, economic and social development of the Canton since its environmentally friendly infrastructure many tourists will choose to choose this site as an option to vacation and thus also They will be able to get to know Quevedo a little more, as well as an excellent service should be given to people so that they can feel satisfied and decide to return to the city.